Oman Student Assessment : SABER Country Report 2013 - World Bank Group (World Bank, Washington, DC, 2016)
Oman has focused on increasing student learning outcomes by improving the quality of education in the country. An effective student assessment system is an important component of efforts to improve education quality and learning outcomes because it provides the necessary information to meet stakeholders’ decisionmaking needs. In order to gain a better understanding of the strengths and weaknesses of its existing assessment system, Oman decided to benchmark this system using standardized tools developed under The World Bank’s Systems Approach for Better Education Results (SABER) program. SABER is an evidence-based program to help countries systematically examine and strengthen the performance of different aspects of their education systems. The key policy areas for the student assessment status are as follows: (i) Classroom Assessment; (ii) Examinations; (iii) National Large-Scale Assessment (NLSA); and (iv) International Large-Scale Assessment (ILSA).